2022
DOI: 10.1111/ggi.14385
|View full text |Cite
|
Sign up to set email alerts
|

Community intervention programs prolong the onset of functional disability among older Japanese

Abstract: Aim This study examined the effects of a “community‐based center” intervention to prevent the onset of functional disability among residents in disaster‐affected areas. Methods We used data from a prospective cohort study conducted from 2010 to 2016 in Iwanuma City, Japan. Participants were community‐dwelling independent adults aged ≥65 years. The exposure variable was the experience of using a community‐based center. The outcome variable was functional disability onset. The average treatment effect on the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Our mediation analyses suggested that the associations between material damage and fear of falling/falls were partly mediated by IADL ( Table 4 ), providing support for this interpretation. In this regard, previous studies showed associations between disaster damage and functional disability ( Hikichi et al, 2021 ; Yamamoto et al, 2022 ). Our work advanced this line of research by further linking disaster damage to falls and pointing to the mediating effect of functional disability in this relationship.…”
Section: Discussionmentioning
confidence: 88%
“…Our mediation analyses suggested that the associations between material damage and fear of falling/falls were partly mediated by IADL ( Table 4 ), providing support for this interpretation. In this regard, previous studies showed associations between disaster damage and functional disability ( Hikichi et al, 2021 ; Yamamoto et al, 2022 ). Our work advanced this line of research by further linking disaster damage to falls and pointing to the mediating effect of functional disability in this relationship.…”
Section: Discussionmentioning
confidence: 88%